A comparison of the impact on neuronal transcriptome and cognition of rAAV5 transduction with three different doses in the mouse hippocampus - Liu, Yi-Si; Wang, Meng-Ling; Hu, Neng-Yuan; Li, Zi-Ming; Wu, Jia-Li; Li, Hao; Li, Jing-Ting; Li, Xiao-Wen; Yang, Jian-Ming; Gao, Tian-Ming; Chen, Yi-Hua (Frontiers in Molecular Neuroscience, 2023)
Gene therapies most commonly utilize recombinant adeno-associated virus (rAAV) vectors as the preferred viral vectors. However, the effects of rAAV transduction with different doses on molecular and behavioral changes are poorly understood. Here we systematically analyzed the transcriptome, glial response and behavior outcome of stereotype rAAV5 transduction with three different doses in the mouse hippocampus. We found that 2.88 × 10 10 v.g rAAV5 transduction significantly upregulated genes related to the immune response and apoptosis, and downregulated genes associated with mitochondrial function and synaptic plasticity in hippocampal pyramidal neurons, while did not induce neuronal loss and gliosis compared with 2.88 × 10 9 v.g and 2.88 × 10 8 v.g. Furthermore, the same doses impaired working memory and contextual fear memory, without effects on locomotion and anxiety-related behaviours. This study suggests that the doses of rAAV5 should take into account in preclinical and clinical studies targeting the hippocampus.